Input and Leaching Potential of Copper, Zinc, and Selenium in Agricultural Soil from Swine Slurry - Comas, Jordi; Domínguez, Carmen; Salas-Vázquez, Dora I; Parera, Juan; Díez, Sergi; Bayona, Josep M (Archives of environmental contamination and toxicology, 2014)
Trace elements, such as copper, zinc, and selenium, used as feed additives were determined in samples of both fresh (N = 14) and anaerobically digested (N = 6) swine slurry collected on medium- to large-size farms in northeast Spain. Considering both fresh and anaerobically digested samples, mean concentrations of zinc (1,500 mg kg⁻¹ dry mass [dm]) were greater than those of copper (mean 239 mg kg⁻¹ dm), and the selenium concentrations detected were even lower (mean 139 μg kg⁻¹ dm). Zinc concentrations were significantly greater in anaerobically digested samples, whereas no significant differences were found for copper or selenium. In addition, the leaching potential of zinc, copper, and selenium in cropped (lettuce heart) and uncropped experimental units subject to drip irrigation was assessed in a greenhouse experiment. Generally, the addition of swine slurry to soil (1.7 g kg⁻¹ dm) significantly increased zinc, copper, and selenium concentrations in leachates, which decreased in accordance with the volume of leachate eluted. Under the experimental conditions, the leaching potential of zinc and selenium was more strongly correlated with bulk parameters directly associated with the composition of the pig slurry (dissolved organic carbon, electrical conductivity, and ammonium), whereas copper mobility was more strongly associated with the crop root exudates. Although selenium has been shown to be mobile in soil, the selenium content found in the leachates did not pose any appreciable risk according to current drinking water standards.